2018
DOI: 10.5740/jaoacint.17-0339
|View full text |Cite
|
Sign up to set email alerts
|

Multimycotoxin Analysis by LC-MS/MS in Cereal Food and Feed: Comparison of Different Approaches for Extraction, Purification, and Calibration

Abstract: Twelve different approaches commonly used for the simultaneous LC tandem MS (MS/MS) determination of mycotoxins (deoxynivalenol, aflatoxins, ochratoxin A, T-2 and HT-2 toxins, fumonisins, and zearalenone) were tested in cereals and feed materials. They comprised different extraction solvents, types of cleanup [solid-phase extraction, QuEChERS, and immunoaffinity (IMA)], and calibration approaches (external or matrix-matched). The percentage of mycotoxins with acceptable recovery, according to Regulation (EC) N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The matrix matched calibration curve (which is restricted to one or two sample types analyzed per batch with the additional requirement to have blank matrices available for spiking purposes) or standard addition (requiring several extractions for one single analysis) quantifications are indeed time consuming, not user friendly, and not adapted for laboratories dealing with a broad range of food matrices on a daily basis. The use of labelled ISTD also improves method precision and accuracy, as recently highlighted in a study evaluating different approaches (extraction, clean-up, quantification) for mycotoxins determination in cereals [27]. The best performances were achieved by a method making use of 13 C-labeled internal standards for quantification.…”
Section: Resultsmentioning
confidence: 99%
“…The matrix matched calibration curve (which is restricted to one or two sample types analyzed per batch with the additional requirement to have blank matrices available for spiking purposes) or standard addition (requiring several extractions for one single analysis) quantifications are indeed time consuming, not user friendly, and not adapted for laboratories dealing with a broad range of food matrices on a daily basis. The use of labelled ISTD also improves method precision and accuracy, as recently highlighted in a study evaluating different approaches (extraction, clean-up, quantification) for mycotoxins determination in cereals [27]. The best performances were achieved by a method making use of 13 C-labeled internal standards for quantification.…”
Section: Resultsmentioning
confidence: 99%
“…In this bracket of retention time (where methanol concentration is high in the LC gradient programme), the matrix effect can be higher and very different for feed samples and in potential effect on immunoaffinity columns. Reduction of the matrix effect can be obtained using labeled internal standards (Figure ) .…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the degradation of those analytes during sample preparation [24,25]. This phenomenon was not observed in the study of Solfizzo et al [20].…”
Section: Comparison Of Validation Parametersmentioning
confidence: 95%
See 1 more Smart Citation
“…Multi-mycotoxin extractions were prepared by using three different sample preparation techniques in corn. Immunoaffinity (method A) [23], solid-phase extraction (method B) [24] and QuEChERS (quick, easy, cheap, effective, rugged and safe) (method C) [25,26] methods applied for this study are shown in Table 1. They were evaluated based on analyte recovery (Rec.)…”
Section: Optimization Of Extraction Processmentioning
confidence: 99%